Influence of Incentives on Employee Performance at UD. Naga Mas Kecap Dua Jempol Gowa - Muh Aldi Rajab; Aslinda Aslinda; Sirajuddin Saleh (Public Resource Innovation Management and Excellence, 2024)
This study aims to find out how the description and how much influence incentives have on employee performance at UD. Naga Mas Kecap Dua Jempol Gowa. To achieve this goal, the researchers used indicators to measure these variables. The indicator variables used are performance, length of service, seniority, needs, fairness, and job evaluation. As for employee performance variables, the indicators used are quality of work, quantity of work, execution of tasks, and responsibilities. In this study, the method used is quantitative method, with data collection namely observation, questionnaires and documentation that are tested for validity and reliability. The sample used is a saturated sample technique with data analysis techniques using the SPSS assistance program which consists of simple linear regression test, correlation coefficient, t test and coefficient of determination. The results showed that the indicators used for each variable showed that employee incentives and performance at UD. Naga Mas Kecap Dua Jempol Gowa is in the very good category. In addition, the results of a simple linear regression test, obtained positive results, and it can be said that incentives affect employee performance. In addition, the results of the correlation coefficient indicate that there is a strong relationship between incentives and employee performance, and shows a positive direction of relationship, meaning that the higher the incentive, the higher the employee's performance. The results of the calculation of the t test and the coefficient of determination, obtained significant results, meaning that there is an incentive effect on employee performance and has a significant effect.